2021
DOI: 10.3390/molecules26175224
|View full text |Cite
|
Sign up to set email alerts
|

(+)-Usnic Acid as a Promising Candidate for a Safe and Stable Topical Photoprotective Agent

Abstract: The study aimed to examine whether usnic acid—a lichen compound with UV-absorbing properties—can be considered as a prospective photoprotective agent in cosmetic products. Moreover, a comparison of two usnic acid enantiomers was performed to preselect the more effective compound. To meet this aim, an in vitro model was created, comprising the determination of skin-penetrating properties via skin-PAMPA assay, safety assessment to normal human skin cells (keratinocytes, melanocytes, fibroblasts), and examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…The highest inhibition of proliferation was noted for HTB140 cells (Figure 2A) and the effect was especially apparent after 72 h of incubation (IC50 19.9 µg/mL and 31.1 µg/mL for (+)-and (−)-usnic acid, respectively). Also, the most significant differences 0.43 Pharmaceuticals 2021, 14,945 For HTB140 cells, a strong antagonism was observed for (+)-usnic acid with doxorubicin, with the tendency to change into additive after longer incub while the effect for (−)-usnic acid changed from synergistic (24 h) through ad finally antagonistic (48 h). Thus, even though each cell line responded differe combination of usnic acid enantiomers with doxorubicin, our results indicate th of the drug may be reduced.…”
Section: (+)-Usnic Acid Inhibited Proliferation Of Melanoma Cells More Effectively Than (−)-Usnic Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest inhibition of proliferation was noted for HTB140 cells (Figure 2A) and the effect was especially apparent after 72 h of incubation (IC50 19.9 µg/mL and 31.1 µg/mL for (+)-and (−)-usnic acid, respectively). Also, the most significant differences 0.43 Pharmaceuticals 2021, 14,945 For HTB140 cells, a strong antagonism was observed for (+)-usnic acid with doxorubicin, with the tendency to change into additive after longer incub while the effect for (−)-usnic acid changed from synergistic (24 h) through ad finally antagonistic (48 h). Thus, even though each cell line responded differe combination of usnic acid enantiomers with doxorubicin, our results indicate th of the drug may be reduced.…”
Section: (+)-Usnic Acid Inhibited Proliferation Of Melanoma Cells More Effectively Than (−)-Usnic Acidmentioning
confidence: 99%
“…Pharmaceuticals 2021, 14,945 For HTB140 cells, a strong antagonism was observed for (+)-usnic acid with doxorubicin, with the tendency to change into additive after longer incuba while the effect for (−)-usnic acid changed from synergistic (24 h) through ad finally antagonistic (48 h). Thus, even though each cell line responded differe combination of usnic acid enantiomers with doxorubicin, our results indicate th of the drug may be reduced.…”
Section: 37mentioning
confidence: 99%
See 1 more Smart Citation
“…Following the prospective results obtained for usnic acid in our previous studies on normal and cancer skin cells, [12,14] we decided to determine the cytotoxic potential of Cladonia mitis acetone extracts and to compare it with the impact of usnic acid alone. In the present study we used 19 Cladonia mitis samples, collected along the North‐South European transect, in which the usnic acid content was determined in our previous work [10] .…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, (+)-UA in combination with octocrylene showed enhanced photoprotective properties and improved photostability. The authors concluded that (+)-UA can be used in cosmetic products as a UV filter [ 63 ].…”
Section: Topical Use Of Uamentioning
confidence: 99%